Economic burden of musculoskeletal disorders in Tanzania: results from a community-based survey - Stefan Siebert; Emma McIntosh; Manuela Deidda; Richard Walker; Ping-Hsuan Hsieh; Blandina Mmbaga; Clive Kelly; Kajiru Kilonzo; Eleanor Grieve; Elizabeth F Msoka; Kiula Kiula; Nateiya Yongolo; et al. (BMJ Open)
Objectives To identify, measure and value the economic burden of musculoskeletal (MSK) disorders in the Kilimanjaro region, Tanzania.Design Community-based cross-sectional survey (undertaken between January and September 2021).Setting Hai district, Kilimanjaro, Tanzania.Participants Households resident in the Hai district.Methods A two-stage cluster sampling was used to select a representative sample of all Hai district residents. Clinical screening tools were used to identify and measure MSK disorders through a tiered approach. An economic questionnaire measuring healthcare costs, out-of-pocket costs, absenteeism, presenteeism and work productivity loss was administered to those with likely MSK disorders and selected controls (individuals without MSK disorders, matched by age and gender). Resource use was valued using country-specific costs. Two-part model regressions were fitted. A descriptive analysis of catastrophic expenditure was also conducted.Main outcome measure Healthcare costs, productivity costs and total costs.Results Annual average productivity and healthcare costs were, respectively, 3.5 and 3 times higher for those with likely MSK disorders than controls. Productivity costs of individuals with MSK disorders were Int$487 vs Int$132 in the control group (difference: Int$355, 95% CI Int$222 to Int$488). Healthcare costs in those with MSK were Int$269 vs Int$88 in the control group (difference: Int$181, 95% CI Int$34 to Int$327). The difference in terms of out-of-pocket expenses was economically substantial in magnitude, although not statistically significant.Conclusion The evidence will be used to inform policies addressing MSK disorders, by promoting the design of interventions, service provision, health promotion and awareness activities at local, regional and national level.